INVESTIGATION OF REQUIREMENTS AND LEGAL FRAMEWORK OF INTEGRATED MANAGEMENT OF THE PERSIAN GULF COAST IN IRAN TO PRESENT IDEAL LEGAL MODELS - Jalali, Ronak; Taghizadeh Ansari, Mostafa; Pournouri, Mansour; Farshchi, Parvin (Gênero & Direito, 2020)
Coastal zones are the most productive and dynamic zones of the world and the bed for big economic and social activities at the world. Along with increased population and development of activities in these fields over the past decades, high pressure has been imposed on these zones and they have been exposed to types of pollutions and destructions. Iran's coasts are not also an exception and especially Persian Gulf Coasts have been exposed to types of pollutions and development of land uses beyond the tolerance of these zones. Hence, over the past years, some efforts have been taken to improve the conditions and the conditions dominated on this field. In this regard, wide exploitations in field of fishery, tourism, business transportation and other fields can double the importance of integrated management of Persian Gulf Coasts. With approval of article 63 of The Fourth Development Plan Act and its Executive Code, it is expected that the problems with Iranian coasts can be solved generally and the Persian Gulf coasts can be organized specially based on the executive mechanisms and the obligations predicted for executive systems in the regulations. The organization process should be the result of studying and planning in frame of environmental integrated management process.